Assessing the impact of infrastructure projects on global sustainable development goals. Issue 4 (28th November 2019) - Mansell, Paul; Philbin, Simon P; Broyd, Tim; Nicholson, Ian
Abstract : While the sustainability of civil infrastructure is critical to professionals, project owners, regulators, funding agencies and the public, little is done to link individual project sustainability to the UN's 17 global sustainable development goals for 2030. This paper not only provides some answers, but also exposes many questions that need resolution by the infrastructure sector. Using empirical evidence, the authors have identified a 'golden thread' between best-practice sustainability-reporting frameworks at the project level and those at the organisational level. In doing so, they have found that there is sufficient linkage to embed sustainable-development-goal impact targets into the design stage of an infrastructure project. This would provide a more robust investment appraisal at the project design phase, helping define project success more widely across the triple bottom line of economic, social and environmental outcomes and associated impact.